2020
DOI: 10.1002/jhet.3855
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel quinoline‐thiosemicarbazide hybrids and evaluation of their biological activities, molecular docking, molecular dynamics, pharmacophore model studies, and ADME‐Tox properties

Abstract: In the present study, a novel series of N‐((substituted)carbamothioyl)‐2,4‐dimethylquinoline‐3‐carboxamide (7a‐7s) was synthesized by microwave‐assisted method. Structure of these derivatives was examined by spectroscopic techniques such as 1H NMR, 13C NMR, FT‐IR, and ESI‐MS. Further, the novel synthesized compounds were evaluated for their in‐vitro biological activities against antibacterial, antifungal, antimalarial, and antituberculosis activity as well as for in‐silico study. The antimalarial results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Therefore, the availability of ligand data is essential to the construction of pharmacophore models. In recent years, there have been many cases of using pharmacophore models to screen promising compounds with outstanding ADMET properties (Nandekar et al, 2016 ; El-Zahabi et al, 2019 ; Mohan et al, 2020 ; Patel D. B. et al, 2020 ; Rawat and Verma, 2020 ). For example, Nandekar et al ( 2016 ) generated and validated a pharmacophore model to screen anticancer compounds acting via cytochrome P450 1A1 (CYP1A1).…”
Section: In Silico Approachesmentioning
confidence: 99%
“…Therefore, the availability of ligand data is essential to the construction of pharmacophore models. In recent years, there have been many cases of using pharmacophore models to screen promising compounds with outstanding ADMET properties (Nandekar et al, 2016 ; El-Zahabi et al, 2019 ; Mohan et al, 2020 ; Patel D. B. et al, 2020 ; Rawat and Verma, 2020 ). For example, Nandekar et al ( 2016 ) generated and validated a pharmacophore model to screen anticancer compounds acting via cytochrome P450 1A1 (CYP1A1).…”
Section: In Silico Approachesmentioning
confidence: 99%
“…Hybrid 51 also acted by inhibiting cell invasion by the parasites, as revealed by the infection rate measured 4 hours after the addition of parasites to the cells. The chemical structures of these hybrids (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59) are given in Fig. 9 and their IC 50 values are shown in Table 7.…”
Section: Artemisinin-primaquine Hybridsmentioning
confidence: 99%
“…15 It has been reported that quinoline molecular framework embellished with styryl motif show HIV integrase inhibitor activity. 16 It is evident from the literature that heterocyclics that contain quinolones, 17 carbazoles, 18 azepinones 19 etc. in their molecules exhibit a wide variety of biological activities such as, anti-mycobacterial, 20 anti-leishmanicidal, 21 antitumor, 22 anti-proliferative 23 and anti-leukemic 24 etc.…”
Section: Introductionmentioning
confidence: 99%